Implementasi Algoritma Naïve Bayes Dalam Klasifikasi Produk – Produk Terlaris - Pipin Octavia (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2024)
PT BRI Finance South Sumatra Branch is a financial company with partners throughout South Sumatra and competitors throughout South Sumatra. PT BRI Finance has new cars, used cars, and refinancing financing products, and each product has special programs such as Advance Payment Installments (ADDM) and Advance Payment Installments (ADDB). One application of the Naive Bayes algorithm is to determine the classification of sales, namely by determining the hierarchical classification of sales. A total of 900 customers as test data generated by this study that customers chose ADDM products as many as 84 or around 22.8%. The value of the performance vector accuracy rate to determine the success rate of naïve Bayes prediction is 74.67% success.